2018
DOI: 10.1111/bph.14184
|View full text |Cite
|
Sign up to set email alerts
|

A two‐state model for the kinetics of competitive radioligand binding

Abstract: Background and PurposeLigand–receptor binding kinetics is receiving increasing attention in the drug research community. The Motulsky and Mahan model, a one‐state model, offers a method for measuring the binding kinetics of an unlabelled ligand, with the assumption that the labelled ligand has no preference while binding to distinct states or conformations of a drug target. As such, the one‐state model is not applicable if the radioligand displays biphasic binding kinetics to the receptor.Experimental Approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Although it needs to be confirmed in future pharmacological studies, we speculate that A preferentially binds to the mGluR5 allosteric site based on the ability of mGluR5 NAM to reverse A-induced changes in neuronal cultures and the incomplete displacement of the radioactive ligand by A. However, the latter can also be attributed to the existence of two populations of receptors that exhibit different MPEP affinities, such that mGluR5 may exist in two conformational states, with A likely selectively binding to the high-affinity site, or that a less accessible MPEP binding site may exist (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although it needs to be confirmed in future pharmacological studies, we speculate that A preferentially binds to the mGluR5 allosteric site based on the ability of mGluR5 NAM to reverse A-induced changes in neuronal cultures and the incomplete displacement of the radioactive ligand by A. However, the latter can also be attributed to the existence of two populations of receptors that exhibit different MPEP affinities, such that mGluR5 may exist in two conformational states, with A likely selectively binding to the high-affinity site, or that a less accessible MPEP binding site may exist (41).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting, these mutant receptors N148S EL2 and V152L EL2 showed lower potency and affinity of CPA compared to the wild‐type hA 1 AR. Moreover, mutant receptor A151V EL2 preferred a one‐site CPA binding model with decreased affinity, which showed that the equilibrium was shifted to one certain receptor conformation, most likely G protein uncoupled 43 . Interestingly, mutant receptors N148S EL2 , A151V EL2 , and V152L EL showed a significantly lower affinity of DPCPX.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentalists are encouraged to use the MC simulations presented here for detailed evaluation of their own procedures (adjustments may be necessary if they differ significantly from the kPCA assay set‐up, Schiele et al, ) and to address the remaining open questions, such as the influence of ligand and target depletion. Along these lines, further studies could include the expansion of these analyses to recent variants of the “kinetics of competitive binding” equation that incorporate alternative scheduling of the labelled and unlabelled ligand addition (Hoare, ; Shimizu, Ogawa, & Nakayama, ) or two‐state binding (Guo et al, ). All in all, this work should enable the optimised design and analysis of competition association assays.…”
Section: Discussionmentioning
confidence: 99%